2017
DOI: 10.1002/ecy.2047
|View full text |Cite
|
Sign up to set email alerts
|

Trait–fitness relationships determine how trade‐off shapes affect species coexistence

Abstract: Trade-offs between functional traits are ubiquitous in nature and can promote species coexistence depending on their shape. Classic theory predicts that convex trade-offs facilitate coexistence of specialized species with extreme trait values (extreme species) while concave trade-offs promote species with intermediate trait values (intermediate species). We show here that this prediction becomes insufficient when the traits translate non-linearly into fitness which frequently occurs in nature, e.g., an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 60 publications
(120 reference statements)
0
48
0
Order By: Relevance
“…Furthermore, the type of defense costs regarding competitiveness (resource uptake affinity or growth rate) plays an important role for coexistence. Theory already showed that predator‐mediated coexistence crucially depends on the environmental conditions (Chase et al., 2002), for example, the enrichment level (Genkai‐Kato & Yamamura, 1999; Leibold, 1996; Proulx & Mazumder, 1998), the prey switching behavior of the predator (Abrams & Matsuda, 1993; Fryxell & Lundberg, 1994; Murdoch, 1969), the magnitude of the trade‐off between defense and competitiveness (Abrams, 1999; Kasada, Yamamichi, & Yoshida, 2014; Tirok & Gaedke, 2010), and the difference in both the defense level and the competitiveness between the prey types (Becks, Ellner, Jones, & Hairston, 2010; Ehrlich, Becks, & Gaedke, 2017; Jones & Ellner, 2007). However, the role of different defense mechanisms and competition costs in prey communities remains unclear but holds promise to be decisive for their coexistence and the occurring population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the type of defense costs regarding competitiveness (resource uptake affinity or growth rate) plays an important role for coexistence. Theory already showed that predator‐mediated coexistence crucially depends on the environmental conditions (Chase et al., 2002), for example, the enrichment level (Genkai‐Kato & Yamamura, 1999; Leibold, 1996; Proulx & Mazumder, 1998), the prey switching behavior of the predator (Abrams & Matsuda, 1993; Fryxell & Lundberg, 1994; Murdoch, 1969), the magnitude of the trade‐off between defense and competitiveness (Abrams, 1999; Kasada, Yamamichi, & Yoshida, 2014; Tirok & Gaedke, 2010), and the difference in both the defense level and the competitiveness between the prey types (Becks, Ellner, Jones, & Hairston, 2010; Ehrlich, Becks, & Gaedke, 2017; Jones & Ellner, 2007). However, the role of different defense mechanisms and competition costs in prey communities remains unclear but holds promise to be decisive for their coexistence and the occurring population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…For scenario (d), we assume that the prey defence arises at the cost of reduced competitiveness and the prey population maintains a polymorphism of defended and undefended individuals. This polymorphism can lead to eco-evolutionary feedback dynamics cycles might be stabilized through prey evolution where the defended prey replaces the undefended over time (Figure 1, scenario (c), Becks, Ellner, Jones, & Hairston, 2010;Ehrlich, Becks, & Gaedke, 2017;Jones & Ellner, 2004, Yoshida et al, 2003.…”
Section: Eco-evolutionary Dynamics In a Predatorprey Systemmentioning
confidence: 99%
“…Depending on the trait-fitness relationship in the specific system, the invader will out-compete the defended prey, the undefended prey or both, which will lead to a change in the population dynamics (see figure 4 in Ehrlich et al, 2017).…”
Section: Increase In Genetic Variationmentioning
confidence: 99%
See 2 more Smart Citations